INCREASING COMPETENCE OF MIDWIFERY STUDENTS IN PERINEAL WOUND SUTURING USING LOW COST MODEL MADE FROM FLANNEL FABRIC - Iswantoro, Rery Kurniawati Danu; Yuningsih, Nani; Rohaeti, Ayi Tansah; Widyawati, Melyana Nurul (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Competence of postpartum perineum wound suturing should be owned by midwives. However, students are limitedly trained on how to use cotton pads that are less representative in form and material. This results in a lack of student competence in perineum stitching practice. Aims: This study goal is to know the effectiveness of perineum wound suturing model made from flannel in order to increase stitching competence on the students of Midwifery study program of Banten Health Polytechnic. Methods: This research was designed using experimental design with post-test design method. The respondents consisted of 11 treatment group and 14 control group. The research implementation consisted of three stages. First, an introduction to the perineum wound sewing technique. Second, the model group practiced with flannel and cotton. Third, the respondents filled up the questionnaire on level of confidence and competence assessment of both groups of students. Data analysis used Mann Whitney test because the median difference of two independent groups if the dependent variable data scale is ordinal and ratio. Results: The results showed that the mean of perineum wound suturing competence in the model group was higher (83) than in the non-model group (74). The statistical test results obtained p = 0.002 which means that there was a significant difference in the competency of both groups. At the self confidence level of the respondents in performing perineum wound suturing, both groups had the same mean (4) with p = 0.651. At the time of perineum wound suturing, it is known that the model group mean was slightly faster (20 minutes) than the non-model group (22 minutes) with p = 0.978. There were no significant differences between the two variables. Conclusion: The study showed that the test model was better in improving the competence of the perineum wound suturing. Flannel model is also more affordable and can be sutured over and over so it is economical for students. Further study on efficient media is recommended so that duration and confidence would be better.Â